2018
DOI: 10.15698/cst2018.10.157
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes, emerging stars of energy homeostasis

Abstract: Astrocytes have historically been considered structural supporting cells for neurons. Thanks to new molecular tools, allowing specific cell ablation or over-expression of genes, new unexpected astrocytic functions have recently been unveiled. This review focus on emerging groundbreaking findings showing that hypothalamic astrocytes are pivotal for the regulation of whole body energy homeostasis. Hypothalamic astrocytes sense glucose and fatty acids, and express receptors for several peripheral hormones such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 104 publications
(129 reference statements)
0
6
0
Order By: Relevance
“…Glucose is the primary energy substrate of not only neurons but also microglia [ 10 ]. Glucose sensing by hypothalamic neurons, astrocytes, and tanycytes is an important component of CNS regulation of whole-body metabolism [ 11 , 12 ]. Previous studies have demonstrated that central administration of the pro-inflammatory cytokine interleukin-1 (IL-1) alpha or beta reduces food intake in rodents [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is the primary energy substrate of not only neurons but also microglia [ 10 ]. Glucose sensing by hypothalamic neurons, astrocytes, and tanycytes is an important component of CNS regulation of whole-body metabolism [ 11 , 12 ]. Previous studies have demonstrated that central administration of the pro-inflammatory cytokine interleukin-1 (IL-1) alpha or beta reduces food intake in rodents [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are highly heterogeneous, exhibiting variations in their appearance and functionality across brain regions and even within substructures, such as the hippocampus (Amundson, Goderie, & Kimelberg, 1992; Lin et al, 2017; Wallraff, Odermatt, Willecke, & Steinhäuser, 2004). Astrocytes contribute to a multitude of brain processes by modulating synaptic plasticity and neuronal activity (Alfonso Araque et al, 2014; Rusakov, Bard, Stewart, & Henneberger, 2014; Ullian, Sapperstein, Christopherson, & Barres, 2001), controlling extra‐synaptic space (Flores‐Méndez, Mendez‐Flores, & Ortega, 2016) and neurotransmitter clearance (Rose et al, 2018; Sibille, Pannasch, & Rouach, 2014), regulating cerebral blood flow (Mishra, 2017), ensuring energy supply to neurons, and orchestrating the rhythms of neuronal firing patterns (Camandola, 2018; Lee et al, 2014; Sheikhbahaei et al, 2018; Stobart & Anderson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“… 20 Astrocytes are closely associated with the pathogenesis of neurodegenerative diseases, mood disorders and energy balance. 21 , 22 , 23 Inflammation‐associated GFAP astrocytes interact with neuronal activation. 8 , 9 We also found that neuronal activation and proinflammatory cytokines were reduced following the inhibition of activated astrocytes in the PVN and then VA occurrence was reduced at 24 h after AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes are non‐neuronal cells and historically considered as structural supporting cells for neurons, but recently more and more evidence indicated that astrocyte plays an essential role in maintaining proper neuronal health and function 20 . Astrocytes are closely associated with the pathogenesis of neurodegenerative diseases, mood disorders and energy balance 21–23 . Inflammation‐associated GFAP astrocytes interact with neuronal activation 8,9 .…”
Section: Discussionmentioning
confidence: 99%